Knockout of 'metal-responsive transcription factor' MTF-1 in Drosophila by homologous recombination reveals its central role in heavy metal homeostasis. - Egli, D.; Selvaraj, A.; Yepiskoposyan, H.; Zhang, B.; Hafen, E.; Georgiev, O.; Schaffner, W. (The EMBO Journal, 2003)
'Metal-responsive transcription factor-1' (MTF-1), a zinc finger protein, is conserved from mammals to insects. In the mouse, it activates metallothionein genes and other target genes in response to several cell stress conditions, notably heavy metal load. The knockout of MTF-1 in the mouse has an embryonic lethal phenotype accompanied by liver degeneration. Here we describe the targeted disruption of the MTF-1 gene in Drosophila by homologous recombination. Unlike the situation in the mouse, knockout of MTF-1 in Drosophila is not lethal. Flies survive well under laboratory conditions but are sensitive to elevated concentrations of copper, cadmium and zinc. Basal and metal-induced expression of Drosophila metallothionein genes MtnA (Mtn) and MtnB (Mto), and of two new metallothionein genes described here, MtnC and MtnD, is abolished in MTF-1 mutants. Unexpectedly, MTF-1 mutant larvae are sensitive not only to copper load but also to copper depletion. In MTF-1 mutants, copper depletion prevents metamorphosis and dramatically extends larval development/lifespan from normally 4-5 days to as many as 32 days, possibly reflecting the effects of impaired oxygen metabolism. These findings expand the roles of MTF-1 in the control of heavy metal homeostasis.